Phytochemical and Antimicrobial Evaluations of some Medicinal Plants of Nepal - Chhetri, Himal Paudel; Yogol, Nisha Shrestha; Sherchan, Jyoti; K.C., Anupa; Mansoor, S; Thapa, Panna (Kathmandu University Journal of Science, Engineering and Technology, 2010)
Use of plant based drugs and chemicals for curing various ailments and personal adornment is as old as human civilization. Plants and plant-based medicaments are the basis of many of the modern pharmaceuticals we use today for our various ailments. The aim of the study was to find out the bioactive chemical constituents and to evaluate the antimicrobial activity of the ethanolic extract of traditionally used eight medicinal plants of Nepal. A qualitative phytochemical analysis was performed for the detection of alkaloids, glycosides, terpenoids, steroids, flavonoids, tannins and reducing sugar. The highest yield of ethanolic extract was found in Azadiracta indica (29.08%). Ocimum santrum contained all the chemicals except flavonoids and reducing sugar however the Colquhounia coccinea lacked alkaloids and reducing sugar. The antimicrobial activities of these plants extract were also observed. The extract of Rhododendron setosum and the essential oil of Eucalyptus globulus were most effective against Escherichia coli and Staphylococcus aureus respectively. But the extracts of Azadiracta indica and Elsholtzia fructicosa were found to be most effective against Klebsiella species. Key words: Phytochemical screening; plant extracts; zone of inhibition DOI: 10.3126/kuset.v4i1.2883 Kathmandu University Journal of Science, Engineering and Technology Vol.4, No.1, September 2008, pp 49-54